2002
DOI: 10.1096/fj.02-0425fje
|View full text |Cite
|
Sign up to set email alerts
|

The structural nature of chromosomal instability in colon cancer cells

Abstract: Biological and genetic cell heterogeneity is a landmark of most colorectal cancers and provides a frame for tumor progression as an evolutional process. Classical models have hypothesized that increased genetic instability may contribute to modulating and shaping malignant transformation. This is true for the small subset of colorectal cancers displaying microsatellite instability. For the rest of colorectal tumors, numerical and/or structural chromosomal alterations are the most prominent outcome of genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
(46 reference statements)
7
25
0
1
Order By: Relevance
“…33 When we compared our results to those published in the same CRC cell lines using SKY, 15,27,28 we obtained the same results using both multicolor karyotyping techniques. By comparing karyotypes of these cell lines previously analyzed by G banding carried out in our laboratory, 9,24 we confirmed that M-FISH techniques allow easy characterization of clones, avoiding misidentifications of chromosome markers and allowing us to follow them along clone generations or in vitro culture passages.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…33 When we compared our results to those published in the same CRC cell lines using SKY, 15,27,28 we obtained the same results using both multicolor karyotyping techniques. By comparing karyotypes of these cell lines previously analyzed by G banding carried out in our laboratory, 9,24 we confirmed that M-FISH techniques allow easy characterization of clones, avoiding misidentifications of chromosome markers and allowing us to follow them along clone generations or in vitro culture passages.…”
Section: Discussionsupporting
confidence: 69%
“…To measure the rate of instability of each cell line, which is also shown in Table II, we calculated the maxr of instability. 9 This rate takes into account only nonclonal alterations and assumes that they took place in the last generation (maxr ϭ number of nonclonal alterations/number of cells). This assessment is an indicator of genetic instability irrespective of the viability of cells showing novel genetic alterations that may or may not be transmitted to further generations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations